Self-value of life or cult of means: value alternative - Rubanau, Anatoly V. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The sociocultural tradition is considered, the value basis of which is the dominance of the cult of means in relation to a person to the world and his own life. As an alternative to the cult of the means, the self-integrity and self-worth of the world, man, self is opposed. Institutionalization of the value coordinate system life as means – life as self-value in itself is associated with the name of I. Kant. One of his categorical imperative formulations says: do so that humanity, both in your person and in the face of any other, is always considered by you as a goal and never just as a means.
Keywords: value; tropocratic sociocultural tradition; cult of means; self-worth of life